Risk management in plant investment decisions: risk typology, dimensions and process. Issue 9 (3rd July 2016) - Kumar, Mukesh; Srai, Jagjit Singh; Gregory, Mike
Abstract: Managing risk associated with plant location decisions is a growing concern as companies seek to reassure investors about the robustness of their strategies. However, little attention has been paid to the systematic evaluation of risk associated with new plants. This paper investigates risk management practices in plant investment decisions through detailed case investigations in a cross section of industrial businesses at different levels of maturity in order to observe current practices, identify common principles and to synthesis systematic approaches to risk management. It identifies key risk categories and dimensions of risk management, building on three key bodies of literature – global manufacturing, investment and risk management